Human rights and humanitarian intervention : the legality of the NATO - Yugoslav - Kosovo war (2000)
Hay otros trabajos sobre el mismo tema. "Comparative peace: a look at recent peace agreements" (p. 298-300). "Old laws and new wars: justifying humanitarian war in the Balkans" (p. 310-313)
Keywords: OTAN; Arbitraje internacional; Kosovo; Yugoslavia; Guerra